Mutational analysis of the RB1 gene in patients with unilateral retinoblastoma - Yousef, Yacoub A.; Mohammad, Mona; Baqain, Laith; Al-Hussaini, Maysa; Shanap, Mayada Abu; Halalsheh, Hadeel; Khzouz, Jakub; Jaradat, Imad; Mehyar, Mustafa; Sultan, Iyad; AlNawaiseh, Ibrahim; Shawagfeh, Munir (Frontiers in Medicine, 2024)
Purpose Retinoblastoma, a childhood cancer originating in the retina, is primarily attributed to pathogenic RB1 mutations The aim of this study is to conduct a mutational analysis of the RB1 gene in cases of unilateral Retinoblastoma among individuals within the Jordanian population. Methods In this study, the peripheral blood of 50 unilateral Rb patients was collected, genomic DNA was extracted, and mutations were identified using Next Generation Sequencing (NGS) analysis. Results In this cohort of 50 unrelated patients with unilateral Rb, the median age at diagnosis was eight months (mean, 12 months; range; 2 weeks to 54 months). Twenty-eight (56%) were males, 29 (58%) had the disease in the right eye, 3 (6%) had a positive family history of Rb, and 20 (40%) were diagnosed within the first year of life. RB1 gene pathogenic mutations were detected in 14 out of 50 (28%) patients, indicating germline disease. Among unilateral non-familial cases, 11 out of 47 (23%) were found to have germline RB1 mutations. Overall, five (36%) of the germline cases had the same mutation detected in one of the parents consistent with an inherited disease (four (80%) were of paternal origin); 3 (60%) of these had affected carrier parent, two (40%) had an unaffected carrier parent. Nine (64%) patients had the nonsense mutation, and six (43%) had the mosaic mutation. The significant prognostic factors for positive genetic testing were positive family history (p = 0.018) and age at diagnosis less than 12 months (p = 0.03). At a median of 54 months follow-up, two (4%) patients were dead from distant metastasis. The overall eye salvage rate was 44% (n = 22/50) eyes; 100% for groups A, B, and C, 60% for group D, and none for group E eyes. There was no correlation between the presence of germline mutation and outcome in terms of eye salvage, metastasis, and survival. Conclusion In this study, 28% of patients with unilateral Rb had germline RB1 mutations, of which 43% were inherited, and one-third presented beyond their first year of life. Therefore, molecular screening is critical for genetic counseling regarding the risk for inherited Rb in unilateral cases, including those with no family history, regardless of the age at diagnosis. However, germline mutations did not appear to significantly predict patient outcomes regarding eye salvage, metastasis, and survival.